Implementation of a Digital-Based Accommodation Reservation System for Optimization of PNBP at the Bekasi Hajj Dormitory - Dwi Isti Anggraini; Kunto Ariawan; Asropi Asropi (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The utilization of State-Owned Assets (BMN) at Bekasi Hajj Dormitory and the broader push for public service digitalization have led to the implementation of an online accommodation reservation system, SIASAH. This application stands as the sole digital system across all Hajj dormitories in Indonesia, developed to uphold Good Governance principles by considering effectiveness, efficiency, and transparency in service management, particularly in optimizing Non-Tax State Revenue (PNBP). This study employs a qualitative approach, using the PESTLE analysis model. Data were gathered through interviews with the application developers, reservation and accommodation staff, and service users, complemented by a review of documents such as accommodation usage reports and official website data from Bekasi Hajj Dormitory. The findings indicate that SIASAH has successfully enhanced financial accountability and transparency. However, the system continues to face significant challenges, including public resistance to technology adoption, limitations in human and physical resources, and a sub-optimal integration of environmentally friendly practices. To address these issues, the report recommends a broader marketing strategy via social media platforms, strengthening resource management, and developing digital archiving features. These measures are crucial for ensuring the system's sustainability, improving its efficiency, and elevating the quality of public services provided.